Ответы и объяснения

2016-07-20T01:05:50+00:00
A1 ответ 3
А2 Ответ 1
А3
1/(x+2)-3/(x+1)=x/(x+2)(x+1)
x≠-2 x≠-1
x+1-3x-6-x=0
-3x=5
x=-5/3
Ответ 2
А4
6/x=x+1
x≠0
x²+x-6=0
x1+x2=-1 U x1*x2=-6
x1=-3⇒y1=-2
x2=2⇒y2=3
(-3;-2);(2;3)
Ответ 4
B1
x/(x+3)+(x-4)/(x-3)=1
x≠-3  x≠3
x²-3x+x²-4x+3x-12-x²+9=0
x²-4x-3=0
D=16+12=28
x1=(4-2√7)/2=2-√7
x2=2+√7
C1
(x²+4x+3)(x²+4x-3)=7
(x²+4x)²-9=7
(x²+4x)²-16=0
(x²+4x+4)(x²+4x-4)=0
(x+2)²(x²+4x-4)=0
x+2=0
x=-2
x²+4x-4=0
D=16+16=32
x=(-4-4√2)/2=-2-2√2
x=-2+2√2
Ответ 3 разных корня